Abstract This study deals with the improvement of the students’ achievement by using Outline technique. This research was conducted by applying classroom action research in two cycles. The subject of this research was one of a class in the first year stu - Nova Diana Simbolon; Siti Aisah Ginting (Universitas Negeri Medan, 2014)
ABSTRACT This study attempts to improve students’ achievement in writing Analytical Exposition through Debate Technique. This study was conducted by using classroom action research. The subject of the research was class XI IPA-1 SMAN 1 Pancur Batu consisting of 36 students. The research was conducted in two cycles and consisted of six meetings. The instruments for collecting data were writing tests as the quantitative data and diary notes, observation sheet, and interview sheet as qualitative data. Based on the writing score, students’ scores kept improving in every test. In the first cycle test, the mean of writing score was 61,67. In the second cycle test the mean of writing score was 71,36. Based on diary notes, observation sheet and questionnaire sheet, it was found that students were actively involved in writing process. The result of the research showed that Debate Technique can improve students’ achievement in writing Analytical Exposition. Keywords: Debate Technique, Writing, Analytical Exposition, Action research